An Analysis Translation of Tajak Collection In Ontology " Sebutir Zamrud Di Deru Selat" To "An Emerald Hill By The Sea" By Muhammad Haji Salleh - Rohdearni Wati Sipayung (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This research is titled Analysis of Translation of a Collection of Poems in Ontology "A Sebutir Zamrud di Deru Selat" into "An Emerald Hill by the Sea by Muhammad Haji Salleh". The purpose of this study is to describe the translation techniques applied in translating the text "A Emerald in the Strait of the Strait" into English. This research is oriented to the product or work of translation. The translation units studied are at the level of words, phrases, clauses and sentences. The data used in this study includes the text contained in the book " Sebutir Zamrud di Deru Selat" and its translation in English. The text " Sebutir Zamrud di Deru Selat" as the source text (TSu) and the text "An Emerald Hill by the Sea" as the target text (TSa). This research data collection method is by applying three kinds of data collection techniques, namely document analysis (content analysis). This technique is applied to collect data related to translation. Data analysis techniques in this study began with data collection. The researcher moves between analysis components interactively while continuing to collect data. The next step after the data is collected, researchers only move between the three components of analysis. The data analysis model used is an interactive model of analysis. Based on the results of research on the translation conducted by translators, it was found that there are two translation techniques used, namely addition and subtraction. In addition, it was found 130 sentences with the addition made by translators as many as 190 sentences, so that the overall average of additions made by translators in translating the poem is 1.5%, then the reduction made by translators in translating the poem is equal to 3.85%.